The Implementation of Simultaneous Village Head Implementation Policy in Realizing Participatory, Transparent and Accountable Election Process in Indonesia - Kholid, Wawan Munawar (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
The purpose of this research is to Analyze the implementation of the simultaneous Village Head election policy in realizing a participatory, transparent and accountable election process in Bogor Regency and Arrange a new model of implementing the Village Head Election policy simultaneously in realizing a participatory, transparent and accountable election process in Bogor Regency. This study uses a qualitative research approach with 21 (twenty-one) informants as a snowball technique. Secondary data collection using literature study techniques, and primary data using interview and observation techniques. Implementation of Pilkades policy simultaneously in realizing the process of participatory selection, transparency, and accountability. The implementation of the village head election policy simultaneously in realizing the participatory, transparent and accountable election process in Bogor Regency is not optimal because there are still many problems found. The new model arranged is called the Sultaa Model, this model consists of elements of participation, transparency, and accountability. The model can be applicable if it meets several requirements, namely qualified human resources, adequate facilitation, adequate funding, and effective supervision.